2016
DOI: 10.1101/073171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in DNA methylation with age replicate across diverse human populations

Abstract: 30Aging is associated with widespread changes in genome-wide patterns of DNA methylation. 31Thousands of CpG sites whose tissue-specific methylation levels are strongly correlated with 32 chronological age have been previously identified. However, the majority of these studies have 33 focused primarily on cosmopolitan populations living in the developed world; it is not known if 34 age-related patterns of DNA methylation at these loci are similar across a broad range of human 35 genetic and ecological diversit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Human populations are known to display considerable genetic diversity, but their degree of epigenetic diversity has been poorly studied to date. A few studies have provided an initial assessment of the contribution of genetic factors and gene-by-environment (G 3 E) interactions to the variation of DNA methylation at population level (Carja et al, 2017;Fagny et al, 2015;Fraser et al, 2012;Galanter et al, 2017;Gopalan et al, 2017;Heyn et al, 2013;Moen et al, 2013). In African populations, the differences in DNA methylation levels associated with differences in lifestyle (farming versus hunting and gathering) have been shown to relate mostly to developmental processes and to display strong associations with nearby genetic variants (meQTLs), which are themselves enriched in selection signals (Fagny et al, 2015).…”
Section: Box 1 Population Epigenetics and Immune Responsesmentioning
confidence: 99%
“…Human populations are known to display considerable genetic diversity, but their degree of epigenetic diversity has been poorly studied to date. A few studies have provided an initial assessment of the contribution of genetic factors and gene-by-environment (G 3 E) interactions to the variation of DNA methylation at population level (Carja et al, 2017;Fagny et al, 2015;Fraser et al, 2012;Galanter et al, 2017;Gopalan et al, 2017;Heyn et al, 2013;Moen et al, 2013). In African populations, the differences in DNA methylation levels associated with differences in lifestyle (farming versus hunting and gathering) have been shown to relate mostly to developmental processes and to display strong associations with nearby genetic variants (meQTLs), which are themselves enriched in selection signals (Fagny et al, 2015).…”
Section: Box 1 Population Epigenetics and Immune Responsesmentioning
confidence: 99%
“…Considerable DNAm differences have been found between populations [76][77][78] , but research on age-associated DNAm differences is scarce. One study 79 reported evidence for overlap in age-associated CpGs in two African populations with studies on European-ancestry populations, but more research is needed to map the generalizability of longitudinal DNAm changes among different populations.…”
Section: Enrichment Of Sites With Dnam Sex Differences In Ewass On Prmentioning
confidence: 99%
“…Using a threshold for absolute beta value difference of 0.15, we identified 14,259 differentially methylated CpG sites, with 11,535 sites hyper-methylated in adults vs. children and 2,724 hypo-methylated in adults vs. children (P < 0.01, FDR-adjusted P < 0.05) ( Figure 1B; Additional file 2). (10,13,29) as well as whole blood (20,21,33) (Table 1; Additional file 2). For example, we found hyper-methylation in adults vs. children at the site cg22454769 in the FHL2 locus, and similar findings of hyper-methylation with older age have been reported in whole blood samples (20,21) as well as in studies of isolated monocytes by Tserel et al (29) and Saare et al (10).…”
Section: Age-related Differences In Monocyte Dna Methylation In Kenyamentioning
confidence: 99%
“…Additionally, it is important to take into account the influence that genetic factors and geneenvironment interactions have on the aging epigenome, yet the majority of studies on age-related methylation markers have been performed in populations with European ancestry, and few have been performed in African populations (32,33). Here, we aimed to analyze DNA methylation profiles and innate immune phenotypes and functions of purified monocytes from healthy individuals living in western Kenya, comparing children aged 1-9 years to adults aged [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] years. Participants for this study were enrolled in a larger observational cohort study of naturally acquired immunity to malaria (34,35).…”
Section: Introductionmentioning
confidence: 99%